An Ancient Bulgarian Ritual and the Magic Power of Words - Китанова, Мария (Poznańskie Studia Slawistyczne, 2012)
The ritual „Gramada” is a typical tradition of the Bulgarian ethnic territories that appeared between the end of the 19th and the beginning of the 20th century. It represents a symbolic way of „escorting” (a sort of symbolic funeral) of a dead man, who committed an act unacceptable for the community, upon the world of the dead. The „Gramada” ceremony is observed as piling up some stones on a sacral place so they can form (create) a barrier between the sinner and the righteous. During the ritual, symbolic words and acts are performed as a verbal and nonverbal act of magic. It reveals thebelief of the traditional Bulgarian people in the magical power of words.